Risk management in the system of internal quality assurance of higher education institutions - Maciejczak, Mariusz (Studia Mundi – Economica, 2016)
The concept of risk management is present in quality assurance of higher education institutions in different scope and scale, seeking the rationality of its use in effectiveness and innovation in internal quality assurance systems. The paper argues that the risk management in internal quality assurance could be introduced in different ways, including: top down and bottom up approaches. Based on the case study from Warsaw University of Life Sciences-SGGW it also explains how risk management could be implemented as the innovative tool.